SEPARATE DETERMINATION OF THE AMOUNT OF OIL EXTRACTED BY ONE WELL FROM TWO LAYERS - Nasirov R.N.,; Baimukhasheva G.K.,; Solodovnikov S.P., (Academic Scientific Journal of Chemistry, 2019)
The authors of this article proposed a different sampling technique for determining reservoir productivity. Relative shares of two in common developed layers in the general output of one production well are determined by vanadium content in oil of several neighboring wells working at each of productive layers separately. Results of experiments on mixture of oil of different layers of the Kalamkas field showed that concentration of vanadium changes in proportion to a volume ratio of oil that confirms competency of such offer. Proposed method was approved in Martyshi and Southeast Kamyshitov multi-layer deposits. The flow rate of the studied reservoirs according to EPR spectroscopy data is in good agreement with the field data. Unconditional advantages of the EPR method are its productivity providing a possibility of receiving the express – information, higher precision and reliability in comparison with the listed methods and no need to stop production wells when sampling oil for a research.